Efficient bilateral trade via two-stage mechanisms: Comparison between one-sided and two-sided asymmetric information environments - KUNIMOTO, Takashi (Institutional Knowledge at Singapore Management University, 2022)
This paper first considers a bilateral-trade model with one-sided asymmetric information in which one agent (seller) initially owns an indivisible object and is fully informed of its value, while the other agent (buyer) intends to obtain the object whose value is unknown to himself. As no mechanisms can generally result in efficient, voluntary bilateral trades (Jehiel and Pauzner, 2006), we aim to overturn this impossibility result by employing two-stage mechanisms (Mezzetti, 2004) in which first, the outcome (e.g., allocation of the goods) is determined, then the agents observe their own outcome-decision payoffs, and finally, transfers are made. We show that the generalized two-stage Groves mechanism and the shoot-the-liar mechanism both induce efficient, voluntary bilateral trades. We next consider a two-sided asymmetric information setup in which both parties have private information. We show by means of a stylized example that the shoot-the-liar mechanism “sometimes” induces an efficient, voluntary trade, while the generalized two-stage Grove mechanism never induces it.